Møter og mangfold Religion og kultur i historie, samtid og skole - Valen Kleive, Hildegunn; Gamborg Lillebø, Jonas; Saether, Knut-Willy (Religionsfag Profil, 2022)
How should cultural and religious diversity be understood? What happens when different cultures and religions meet? How should we understand such encounters in society and school today? How have they played out historically? This scholarly anthology elucidates these questions from a variety of perspectives, disciplines and subject areas. The book includes both theoretical and practice-oriented texts. Fundamental questions and conceptual understanding are combined with discussions of encounters and diversity in daily life. The book is written for researchers and students at the bachelor, master and doctoral levels, and anyone interested in questions pertaining to culture, religion and society.